Bleached broilers and divine fowls: The ritual economy of chickens in a South Indian city. Issue 1 (16th February 2023) - Doron, Assa
Abstract : Commercial poultry operations are booming as demand for chicken soars in 21st‐century India. The industry relies on the models familiar from industrial countries: birds pumped with growth hormones and antibiotics designed to ensure rapid, standardized egg production and broiler meat. Nevertheless, during my fieldwork in India, locals insisted that broiler chickens were rarely used for ritual purposes. They explained that the gods were far more discerning and should only be offered the 'country chicken' ( Natu kodi ). The distinctive appearance of these 'rural' birds was seen to make them appropriate for ritual sacrifices, with transformative potential. Even urban dwellers seemed to prefer these much costlier indigenous birds – untouched by the homogenizing logic of industrial livestock production – especially for rituals. As I show in this essay, the ritual economy of chickens illustrates the process of 'metabolic' transformations, toxic entanglements and more‐than‐human encounters, as much as it reveals that of mutualism, with its vital and varied meanings tied to social relations and ecological sensibilities.